2023
DOI: 10.3390/cancers15020428
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Selected Dysregulated microRNAs in Diagnosis and Prognosis of Childhood B-Cell Precursor Acute Lymphoblastic Leukemia

Abstract: B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is a frequent type of childhood hematological malignancy. The disease is classified into several subtypes according to genetic abnormalities. MicroRNAs (miRNAs) are involved in pathological processes (e.g., proliferation, apoptosis, differentiation). A miRNA is a group of short non-coding RNAs with relevant regulatory effects on gene expression achieved by suppression of the translation or degradation of messenger RNA (mRNA). These molecules act as tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Ziętara, K. J.,et al [44] has expressed the acute leukemia causes fever or chills in the legs. But these events never occur in people with chronic leukemia.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziętara, K. J.,et al [44] has expressed the acute leukemia causes fever or chills in the legs. But these events never occur in people with chronic leukemia.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%
“…An increase in the size of the gums is called hyperplasia. These symptoms are usually only seen in a small number of people with acute leukemia Ziętara, K. J.,et al [44] The acute leukemia causes fever or chills in the legs. But these events never occur in people with chronic leukemia.…”
Section: B Analysis Based On Symptomsmentioning
confidence: 99%
“… 8 Recent studies have revealed characteristic expression patterns according to genetic subgroups of pediatric BCP-ALL as well as their prognostic significance. 9 , 10 In addition, novel prognostic factors identified by integrated analysis, including miRNAs and mRNAs, have been reported in several types of malignant tumors 11 ; however, few studies have conducted an integrated analysis focusing on miRNA profiles in a large cohort of pediatric BCP-ALL.…”
Section: Introductionmentioning
confidence: 99%